Pemanfaatan Pembelajaran Daring sebagai Media Pembelajaran Online Mata Kuliah Manajemen Kearsipan pada Mahasiswa Prodi Pendidikan Administrasi Perkantoran Universitas Negeri Surabaya - Felda Rizki Amalia; Durinta Puspasari (Edunusa: Journal of Economics and Business Education, 2021)
This study aims to analyze the use of online learning as an online learning medium for Archives Management courses for students of the Unesa Office Administration Education Study Program. This type of research is descriptive qualitative research. The research subjects were 6 people consisting of 1 lecturer and 5 students of the 2017 Office Administration Education Study Program class A. While the triangulation of sources was 2 people consisting of 1 Archives Management lecturer and 1 2017 Office Administration Education Study Program student class A. Data collection techniques used interviews and questionnaires, while the data analysis technique used is the Analysis Interactive model from Miles and Huberman which divides the analysis activities into several parts, namely: data collection, data reduction, data presentation, and conclusion drawing or data verification. The results showed that for indicators of online learning: 1) most of the Office Administration Education students have facilities in the form of smartphones and laptops to support the implementation of online learning in the Archives Management course; 2) for the Archives Management course, it is better to do conventional learning because it is more practical than theory, but due to the Covid-19 pandemic, the most effective is online learning; 3) reducing the fear of contracting the Covid-19 virus in the campus area can be suppressed by changing conventional learning to online or online learning such as zoom, google meet, WhatsApp groups, or others. As for the indicators of online learning media: 1) the ease of use of the application is being able to use learning videos that can be downloaded at any time to help re-learn the material that has been given; 2) the use of google classroom, google meet, and zoom is considered very effective to support learning activities.